A study on age and growth characteristics of spiny gurnard (Lepidotrigla dieuzeidei Blanc & Hureau, 1973), northeastern Mediterranean Sea - Basusta, A.; Basusta, N.; Calta, M.; Ozcan, E. I. (Wiley, 2017)
This study investigated the age and growth characteristics of spiny gurnard, Lepidotrigla dieuzeidei, from the northeastern Mediterranean. Samples were collected by commercial trawls during the 2012-2013 fishing seasons. A total 1,878 speciments ranged from 7.10 to 15.90cm total length and 2.28-35.88g in weight. Female/male ratio was 1.2/1. The total length-weight relationship was W=0.002 TL3.579 (r(2)=.909) for sexes combined, W=0.0021 TL3.551 (r(2)=.914) for males and W=0.0019 TL3.602 (r(2)=.904) for females. Age determination was conducted using the sagittal otoliths. Ages of examined individulas ranged from 3 to 11years. Total length-at-age data were fitted using the von Bertalanffy growth model. Estimated growth functions were TLt=18.100 [1-e(-0.14 (t+0.63))] for sexes combined, TLt=23.587 [1-e(-0.08 (t+1.56))] for males and TLt=16.612 [1-e(-0.19 (t+0.15))] for females.
Keywords: Triglidae; Linnaeus